Promoted spatial charge separation of plasmon Ag and co-catalyst CoxP decorated mesoporous g-C3N4 nanosheet assembly for unexpected solar-driven photocatalytic performance. (17th September 2019) - Yang, Zekang; Xing, Zipeng; Chi, Dechao; Li, Zhenzi; Sun, Dandan; Du, Xin; Yin, Junwei; Zhou, Wei
Abstract: Plasmon Ag and co-catalyst Co x P decorated mesoporous graphite carbon nitride nanosheet assemblies have been synthesized via a template-calcination and ball milling strategy combined with photoreduction. The obtained composites are characterized by x-ray diffraction, Fourier transmission infrared spectroscopy, x-ray photoelectron spectroscopy, transmission electron microscopy, and UV–vis diffuse reflectance spectroscopy. The results show that the sample assembly with mesoporous structure has specific surface area of 50.4 m 2 g −1, pore size of 11.3 nm and pore volume of 0.21 cm 3 g −1 . The Ag and Co x P nanoparticles are decorated on the surface of graphite carbon nitride uniformly. Under solar light irradiation, the photocatalytic degradation rate of ceftazidime for the prepared sample assembly is up to ∼92%, and the photocatalytic reaction rate constant is about 10 times higher than that of bare graphite carbon nitride. Moreover, the sample assembly also exhibits a solar-driven photocatalytic hydrogen production rate of 96.66 μ mol g −1 h −1 . It can attributed to the surface plasmon resonance effect of Ag nanoparticles and Co x P co-catalyst promoting the spatial charge separation and the mesoporous structure providing more surface active sites and favoring mass transfer. This special structure offers new insights for fabricating other high-performance photocatalysts with high spatial charge separation